2010
DOI: 10.1016/j.jash.2010.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Association between circulating specific leukocyte types and blood pressure: the Atherosclerosis Risk in Communities (ARIC) study

Abstract: Background-Although total white blood cell (WBC) count has been associated with hypertension, the association between specific WBC types and blood pressure (BP) levels has not been studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 58 publications
2
29
0
Order By: Relevance
“…Previous studies have suggested that there is a relation between hypertension and systemic inflammation [12]. The relationship between circulating subtype of white blood cell and hypertension has also been well documented [13,14]. In a large cohort with a long follow-up period, Tatsukawa et al [13] aimed to investigate the relationship between white blood cell count, including differential white blood cell count, and the incidence of hypertension over a 40-year period in 9,383 subjects who did not have hypertension at baseline.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have suggested that there is a relation between hypertension and systemic inflammation [12]. The relationship between circulating subtype of white blood cell and hypertension has also been well documented [13,14]. In a large cohort with a long follow-up period, Tatsukawa et al [13] aimed to investigate the relationship between white blood cell count, including differential white blood cell count, and the incidence of hypertension over a 40-year period in 9,383 subjects who did not have hypertension at baseline.…”
Section: Discussionmentioning
confidence: 94%
“…In another study, SUA was significantly and independently associated with neutrophil count (34). In a recently published study, hyperlipidemia-triggered neutrophilia was shown to promote early atherosclerosis (35 In another recent study, Tian et al (36) searched the association between circulating specific leukocyte types and blood pressure and found that blood pressure is specifically related to N and L. Kawada et al (37) showed an independent relationship between N and hypertension. In the study by Yen et al, the investigators searched the relation between hsCRP, standard CVRFs and WBC, neutrophils and monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Leukocytosis, especially increased neutrophils and decreased lymphocyte count increase BP in Blacks by 6/2 mmHg in the highest vs the lowest tertile [38] . Macrophages and various T-cell subtypes regulate BP, invade the arterial wall, activate TLRs and induce autoimmune vascular damage [38,39] . Angiotensin Ⅱ activates immune cells (T cells, macrophages and dendritic cells) and promotes cell infiltration into target organs [39] .…”
Section: Autoimmune Dysfunctionmentioning
confidence: 91%
“…38 target organ damage (TOD). Nutrient-gene interactions, subsequent gene expression, epigenetics, oxidative stress, inflammation and autoimmune vascular dysfunction have positive or negative influences on vascular biology in humans.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation